IDENTIFIKASI FAKTOR INTERNAL DAN FAKTOR EXTERNAL PENGEMBANGAN PARIWISATA PANTAI NATSEPA DENGAN PENDEKATAN COMMUNITY-BASED TOURISM - Yohana Aprilia de Lima; Aditha Agung Prakoso (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2019)
The purpose of this research is to identify the internal and external factor that obstruct or driven the development of Natsepa beach. This research used descriptive qualitative. The research was focused on identifying internal and external factors of development in Natsepa beach with Community-based tourism as an approach. The results of this study show that there are many physical and non-physical potential that can be developed into marine tourism the place itself is accessible and the government as the management already provide some facilities such as accommodation, etc. Indeed, the existing facilities need to be updated and improved. The potential need to be developed and managed properly, therefore proper planning and synergy among various parties is needed so each of activities can give a positive impact in economic and also environment to every parties.